2023
DOI: 10.1007/s13410-022-01161-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Faecalibacterium prausnitzii and Bifidobacterium is associated with a higher risk of metabolic associated fatty liver disease in young-onset type 2 diabetes

Abstract: Background The incidence of comorbidity between type 2 diabetes mellitus (T2DM) and metabolic-associated fatty liver disease (MAFLD) is high, and patients tend to be younger. When people develop metabolic diseases such as T2DM and MAFLD, the original homeostasis of the gut microbiota in the body is disrupted, and gut flora drift occurs. This study investigated the relationship between the number of gut flora and MAFLD in young-onset T2DM. Methods This retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…Disturbance of gut microbiota was detrimental to the health of the host (Zhang et al, 2015). Furthermore, intestinal microbiota issues are frequently characterized by the considerable reduction of Faecalibacterium prausnitzii and Bifidobacterium (Vijay and Valdes, 2022;Chen et al, 2023); these reports are in according with our finding of decreased Bifidobacterium pseudocatenulatum, Bifidobacterium longum, Bifidobacterium adolescentis, and Faecalibacterium prausnitzii in the SAR group. We found that the abundance of Phascolarctobacterium faecium was down-regulated in the SAR group as a potential probiotic that may be associated with intestinal detoxification.…”
Section: Discussionsupporting
confidence: 88%
“…Disturbance of gut microbiota was detrimental to the health of the host (Zhang et al, 2015). Furthermore, intestinal microbiota issues are frequently characterized by the considerable reduction of Faecalibacterium prausnitzii and Bifidobacterium (Vijay and Valdes, 2022;Chen et al, 2023); these reports are in according with our finding of decreased Bifidobacterium pseudocatenulatum, Bifidobacterium longum, Bifidobacterium adolescentis, and Faecalibacterium prausnitzii in the SAR group. We found that the abundance of Phascolarctobacterium faecium was down-regulated in the SAR group as a potential probiotic that may be associated with intestinal detoxification.…”
Section: Discussionsupporting
confidence: 88%